Understanding Teacher Education Students’ Research Competence Through Their Conceptions of Theory - Salmento, Heidi; Murtonen, Mari; Kiley, Margaret (Frontiers in Education, 2021)
Learning a scientific way of thinking is a fundamental aim of university education. It means that there are certain thinking skills that students across all disciplines should learn during their studies. For example, critical thinking and reasoning skills are essential for all university graduates. In addition, students are expected to achieve certain skill levels related to scientific research, for example: learning the basic concepts of science and research methodology, understanding the research process and understanding the nature and origins of scientific knowledge. We call these skills research competence and see research competence as one of the main elements of scientific thinking. We assume that understanding the basic concepts of science is a starting point for the development of research competence and more broadly, for scientific thinking. However, previous studies have shown that scientific concepts are not easy for students to learn. The aim of this study is to increase our understanding of a particular aspect of university students´ research competence by exploring teacher education students’ (N=179) conceptions of one of these challenging concepts, the concept of theory. The results illustrate that understanding the concept of theory is challenging even for graduating (fourth and fifth year) master students. Only half of them were able to describe the concept of theory in a scientific context suggesting that the other half had unscientific conceptions of theory, named here as non-scientific conceptions. When looking at the students´ who reported scientific conceptions of theory, one quarter of graduating students and a few early stage (first and second year) students had a declarative approach meaning that they were able to describe the concept of theory by using some basic scientific terms. About one fifth of graduating and early stage students had a procedural approach meaning that they were able to describe theory related to research as “doing”. Only a small number of students showed an understanding of the nature and origins of scientific knowledge and the role of research and theory, called here an epistemic approach.